Transparency and Public-Private Collaboration as Solutions to Improve Education Budget Efficiency for Enhancing Education Quality in Indonesia - Hidayah, Jumatul; Murniyanto, Murniyanto; Baron, Michael (Journal of Education and Religious Studies, 2026)
Education plays a highly strategic role in developing competent human resources capable of facing global challenges. However, despite Indonesia's education budget constituting 20% of the national budget (APBN), significant issues persist regarding uneven distribution and inefficiency in fund allocation, particularly in remote areas. Transparent and accountable budget management is crucial to addressing these issues and improving the effectiveness of education budget management in Indonesia. This study aims to analyze relevant education financing models, explore effective budget management practices, and identify challenges and solutions to enhance the efficiency of education budget management. Through an in-depth literature review, the study finds that while Indonesia's education financing model includes substantial funding, inefficiencies in allocation remain, and a public-private partnership model could be a potential solution by improving coordination and transparency. Moreover, effective budget management is hindered by a lack of human resource competence and weak policy oversight. Therefore, enhancing human resource capacity through technology-based training and professional certification is critically needed, especially in remote areas. The study concludes that public-private collaboration and improved systems for more transparent and accountable budget management can enhance the quality of education in Indonesia. Recommendations include strengthening coordination, oversight, and the utilization of information technology.